Health Status of Buddhist Monks in Amphoe Mueang, Changwat Samut Sakhon - Wanichsuwan, Molee (Journal of Health Science of Thailand, 2017)
The objective of this descriptive research was to study monksี health status in Amphoe Mueang, Changwat Samut Sakhon in August 2007. Data was obtained voluntarily from 347 Buddhist monks aged over 35 years who stayed in a single monastery during the rainy season in Amphoe Mueang, Changwat Samut Sakhon. The study group was interviewed to obtain personal information. Health evaluation form (Thai GHQ-28), laboratory test for blood components, urine analysis, and chest X-ray were instrumental in health status assessment of the subjects. Data was analyzed by using descriptive statistics. The results showed that 45.4 percent of interviewees were Buddhist monks aged 35-49 years while 33.7 percent were elderly. The majority of the study group had been ordained for 1-5 years while 30 percent of them for over 15 years. Metabolic syndrome leading to cardiovascular diseases was a critical health problem among them. Of the study group, 47.8 percent were rated, on BMI scale, over nutrition, and 29.1 percent obese on waist circumference. Lipid profile showed that 64.2 percent of the total had hypercholesterolemia, 36.3 percent had excessive triglyceride, and 68.2 percent excessive LDL. Diabetes and high blood pressure patients were receiving treatments only 56.6 percent and 31 percent of them respectively. The rates went higher than those previously reported. In conclusion, the monks were at high risk with cardiovascular disorders and it requires urgent measures to prevent and control, as such, relevant policy, action plan, health indicators in screening programs, diagnostic and treatment should be spelled out for this particular risk group. In addition, their attitude regarding health shoud be studied.